Transformation Of Lecturer Professional Development Through Digital Technology Integration In The Society 5.0 Era - Usman Usman (Doctoral Program of Social Science Pasundan University, 2026)
The digital technological shift in the Society 5.0 era demands that lecturers transform from conventional teachers to adaptive facilitators, innovators, and mentors. The reality on the ground demonstrates structural barriers in the form of low digital literacy, limited regular training, and minimal institutional support, creating a gap between contemporary ideals and actual lecture implementation. This research aims to explore tactical formulations for boosting lecturers' digital competency to anticipate changes in higher education. This research uses a qualitative-descriptive approach based on theories of digital pedagogy, lifelong learning, and technology-based professional development. Using purposive sampling, lecturers and campus management were identified as key informants. Data was collected comprehensively through observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The authenticity of the findings was ensured through data validity testing through source and technique triangulation. Research findings prove that increasing lecturer professionalism is realized through intensive technology training, strengthening virtual academic communities, stimulating internal motivation, and optimizing digital infrastructure.. More than just technical improvements, this transformation demands a reform of mindsets, a reconstruction of academic culture, and the mental readiness of educators to create an interactive, flexible, and student-centered learning atmosphere. Improving the quality of the higher education ecosystem in the modern era depends heavily on the synergy of educator mental readiness and technological facilitation. Consequently, higher education management is recommended to design lecturer development programs that are sustainable, humanistic, collaborative, and responsive to the dynamics of pedagogical technology.